(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Maintaining and improving the health of children and adolescents is a priority for modern society. During childhood and adolescence, fundamental habits are formed, including hygiene habits, which later determine a person’s quality of life. Adherence to personal and public hygiene rules helps prevent infectious diseases, promote healthy physical development, and improve performance.